New Insight into the Interface Chemistry and Stability of Glutathione Self-Assembled Monolayers on Au(111) - Lobo Maza, Flavia Emilia (2016)
In this paper we have studied glutathione (GSH) self-assembled monolayers (SAMs) on Au(111) prepared by incubation from solutions in phosphate buffer (pH = 7). These SAMs degrade with increasing immersion time to yield adsorbed S and polysulfide species on the gold surface, as revealed by cyclic voltammetry and Xray photoelectron spectroscopy. Results from polarization modulation infrared reflection−absorption spectroscopy (PM-IRRAS) show that even if GSH decomposes on the surface the vibrational bands characteristic of the molecule are still present. This has direct relevance for the study of gold nanoparticles (AuNPs) protected by hydrophilic thiols and also for biomedical applications of GSH-capped AuNPs. Thiol exchange experiments of the drug 6- mercaptopurine (6MP) SAMs on Au(111) in contact with GSH solutions were also performed to better understand the possible role of the latter in the triggered release of 6MP from the surface of AuNPs for drug delivery applications. Our results show that 6MP is completely released only when a S adlayer, produced by desulfurization of GSH, is formed on the Au(111) surface.